2015
DOI: 10.1021/ef502380x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative X-ray Fluorescence Analysis of Biomass (Switchgrass, Corn Stover, Eucalyptus, Beech, and Pine Wood) with a Typical Commercial Multi-Element Method on a WD-XRF Spectrometer

Abstract: Quick and reliable inorganic elemental chemical analysis of biomass (incl. solid biofuels) is of importance in the increasing utilization and trade of biomass. In particular, it is important for the exploitation of contaminated / dirty biomass / biomass waste, and potentially also as a tool in ascertaining the type/origin of biomass. X-ray fluorescence (XRF) spectrometry performed directly on the raw biomass with limited prior sample preparation is an attractive method for performing such inorganic elemental a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 26 publications
2
39
0
Order By: Relevance
“…The two reports of XRF-based Si estimation in napiergrass [11,63] have ranged from somewhat lower to somewhat higher than those in this study; however, they were both performed in tropical regions and would not provide relevant yield estimates for subtropical and temperate regions. The single report of XRF-based Si content in switchgrass [64], was based only on bulk biomass samples of unknown origin and without the associated biomass yields.…”
Section: Discussionmentioning
confidence: 99%
“…The two reports of XRF-based Si estimation in napiergrass [11,63] have ranged from somewhat lower to somewhat higher than those in this study; however, they were both performed in tropical regions and would not provide relevant yield estimates for subtropical and temperate regions. The single report of XRF-based Si content in switchgrass [64], was based only on bulk biomass samples of unknown origin and without the associated biomass yields.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been demonstrated that modern X-ray fluorescence instruments can provide data that is comparable to inductively coupled plasma methods for the inorganic composition (major and minor elements) of raw biomass, i.e. without the need to ash the sample [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…X-ray fluorescence analysis (XRF) is a rarely used analytical tool for LCF, although it is an attractive method for performing inorganic elemental analysis [133]. Even if LCF is mainly composed from organic matter and light elements that cannot be detected directly with XRF, an application of chemometric techniques to the scattering XRF profile may provide valuable information on integral LCF parameters.…”
Section: Spectroscopic Data Processing Using Chemometric Methods Formentioning
confidence: 99%